2020
DOI: 10.1055/s-0040-1708570
|View full text |Cite
|
Sign up to set email alerts
|

Drainage Performance of a Novel Catheter Designed to Reduce Drainage Catheter Failure

Abstract: Objective Efficient flow of fluids through drainage/infusion catheters is affected by surrounding tissue, organ compression, and scar tissue development, limiting or completely obstructing flow through drainage holes. In this work, we introduce a novel three-dimensional (3D) drainage catheter with protected side holes to reduce flow blockages. We then compare its drainage performance to standard straight and pigtail catheters using computer-generated catheter designs and flow analysis software. Methods Drainag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Traditionally, two types of hole designs are employed in pigtail catheters: punched holes and skived holes. [2] Punched holes are generally circular and are made by punching through the catheter wall. In contrast, skived holes are cut at an angle, resulting in a more oval shape that is smoother around the edges.…”
Section: Hole Designs: Skived Vs Punchedmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, two types of hole designs are employed in pigtail catheters: punched holes and skived holes. [2] Punched holes are generally circular and are made by punching through the catheter wall. In contrast, skived holes are cut at an angle, resulting in a more oval shape that is smoother around the edges.…”
Section: Hole Designs: Skived Vs Punchedmentioning
confidence: 99%
“…Background and Software Computational Fluid Dynamics (CFD) has proven to be an effective tool for understanding complex fluid dynamics, especially in medical devices such as catheters. [2] We employed a commercial CFD software package for our numerical simulations, which solves the governing equations for fluid flow.…”
Section: Computational Fluid Dynamics Modelmentioning
confidence: 99%
“…Hole Designs: Skived vs. Punched Traditionally, two types of hole designs are employed in pigtail catheters: punched holes and skived holes. [2] Punched holes are generally circular and are made by punching through the catheter wall. In contrast, skived holes are cut at an angle, resulting in a more oval shape that is smoother around the edges.…”
Section: Background and Rationalementioning
confidence: 99%
“…[4] Studies have shown that irregular flow patterns and high turbulence can lead to clogging, requiring catheter replacement and Potentially complicating patient care. [2] Gap in the Literature Despite the ubiquitous application of pigtail catheters in draining a variety of fluid collections, there is a lack of comprehensive studies comparing the fluid dynamics of skived holes and punched holes. Most of the existing literature is focused on the material properties and overall design of catheters , with little attention given to the specific design of the drainage holes and their implications for clinical efficacy.…”
Section: Background and Rationalementioning
confidence: 99%